Gymnopilus purpureosquamulosus Høil. (Agaricales, Basidiomycota): a new distributional record from India - Krishnendu Acharya; Soumitra Paloi; Arun Dutta; Rimpa Sikder; Tulika Saha (Check List, 2017)
Gymnopilus purpureosquamulosus Høil (Strophariaceae) is reported for first time from India. A comprehensive description, a photograph, and comparisons with morphologically similar and phylogenetically related species are provided.